2022
DOI: 10.1101/2022.08.11.503589
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phenotypic Plasticity of Symbiotic Organ Highlight Deep-sea Mussel as Model Species in Monitoring Exploitation of Deep-sea Methane Hydrate

Abstract: Phenotypic plasticity and symbiosis are two key factors influencing the evolution and adaptation. However, knowledge of how symbiotic cells and organs evolve under and adapt to emerging environmental changes is still scarce. Herein, we assessed the long-term phenotypic changes of gill in aposymbiotic deep-sea mussels induced by methane deprivation to clarify the physiological basis that facilitates evolution and adaptation of mussels. We showed that aposymbiotic mussels managed a long survival by digesting sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 105 publications
1
2
0
Order By: Relevance
“…Sterol metabolism in symbionts may be a common mechanism in the development of symbiotic cells and organs since several animal hosts rely on their symbionts for sterol intermediates [74][75][76] . In support of this theory, we noted a suppression of sterol/steroid biosynthesis in the symbiont-depleted deep-sea mussels after long-term atmospheric cultivation without methane supply; furthermore, a crucial sterol metabolic gene was differentially expressed during the maturation of bacteriocytes, highlighting possible participation of sterol metabolism in the phenotypic plasticity of gill tissue 69 . Other studies have also shown the modulation of host development and reproduction by symbiotic Wolbachia via steroid-nuclear receptor signaling pathway 77 .…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Sterol metabolism in symbionts may be a common mechanism in the development of symbiotic cells and organs since several animal hosts rely on their symbionts for sterol intermediates [74][75][76] . In support of this theory, we noted a suppression of sterol/steroid biosynthesis in the symbiont-depleted deep-sea mussels after long-term atmospheric cultivation without methane supply; furthermore, a crucial sterol metabolic gene was differentially expressed during the maturation of bacteriocytes, highlighting possible participation of sterol metabolism in the phenotypic plasticity of gill tissue 69 . Other studies have also shown the modulation of host development and reproduction by symbiotic Wolbachia via steroid-nuclear receptor signaling pathway 77 .…”
Section: Discussionsupporting
confidence: 59%
“…The contradicts in the number of new born endosymbionts and digested endosymbionts suggested that lysosome-mediated digestion could play other roles in addition to providing nutrients. Recently, it is showed that the digestion of symbionts could be regulated by mTORC1 through nutrient signaling pathway and promoted under reduced nutrient supply (either by death of endosymbionts or removal of methane) [40][41][42] . We therefore speculated that lysosome-mediated symbiont digestion may be a secondary option to obtain nutrition under normal circumstance, but an efficient way to control the symbiont population and obtain nutrition under abrupt stresses or other emergencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation